Faktor-Faktor yang Memengaruhi Kualitas Laporan Keuangan Pada Organisasi Perangkat Daerah di Kota Madiun - Immanuela, Intan; Denandra, Fegisa Gayuh (Indonesian Journal Publisher, 2025)
This study aims to analyze the factors influencing the quality of local government financial reports, focusing on the impact of human resource competence, internal control systems, and the utilization of information technology. This quantitative research employed a purposive sampling technique, with the sample comprising finance department staff from Regional Device Organizations (OPD) in Madiun City who have a minimum of one year of work experience. The results indicate that human resource competence and the internal control system have a partially positive and significant effect on the quality of local government financial reports. This finding confirms that the capabilities of personnel and effective internal oversight mechanisms are crucial elements for producing reliable and accountable financial reporting. Conversely, the utilization of information technology was found to have no significant effect, which is suggested to be due to constraints in the optimal implementation of technological infrastructure and user skills. In conclusion, while technology continues to advance, human factors and internal control systems remain the primary predictors of financial reporting quality within the context of this study. It is recommended that future research expand the geographical scope and incorporate other variables to obtain a more comprehensive and generalizable understanding.